1998
DOI: 10.1085/jgp.111.3.421
|View full text |Cite
|
Sign up to set email alerts
|

Uncharged S4 Residues and Cooperativity in Voltage-dependent Potassium Channel Activation

Abstract: Substitution of the S4 of Shaw into Shaker alters cooperativity in channel activation by slowing a cooperative transition late in the activation pathway. To determine the amino acids responsible for the functional changes in Shaw S4, we created several mutants by substituting amino acids from Shaw S4 into Shaker. The S4 amino acid sequences of Shaker and Shaw S4 differ at 11 positions. Simultaneous substitution of just three noncharged residues from Shaw S4 into Shaker (V369I, I372L, S376T; ILT) reproduces the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
200
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(210 citation statements)
references
References 43 publications
8
200
1
Order By: Relevance
“…S 4 hydrophobic residues are involved in K ϩ channel voltagedependent gating (Lopez et al, 1991;McCormack et al, 1991), and it has been proposed that the gating differences between Shaker (K v 1) and Shaw (K v 3) channels are mainly accounted for by sequence differences with respect to S 4 uncharged amino acids (Smith-Maxwell et al, 1998). Uncharged amino acids also occupy the positions corresponding to A196 and L197 in the K v 1.2 voltage-gated K ϩ channel (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S 4 hydrophobic residues are involved in K ϩ channel voltagedependent gating (Lopez et al, 1991;McCormack et al, 1991), and it has been proposed that the gating differences between Shaker (K v 1) and Shaw (K v 3) channels are mainly accounted for by sequence differences with respect to S 4 uncharged amino acids (Smith-Maxwell et al, 1998). Uncharged amino acids also occupy the positions corresponding to A196 and L197 in the K v 1.2 voltage-gated K ϩ channel (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The S4 segment is proposed to function as a voltage sensor with positively charged residues critical in voltage-dependent transitions for activation (36). Recent studies by Smith-Maxwell et al (37,38) suggest that single conserved uncharged amino acid substitution within the S4 region may be important in cooperativity and voltage dependence of Shaker K ϩ channels. These authors demonstrated that substitution of leucine for isoleucine (that differ in the attachment of a methyl group) resulted in changes in the gating charge movement.…”
Section: Discussionmentioning
confidence: 99%
“…1 implies that the correlation between j out and V 1/2 depends on the variability of j in þ G 0 /F. This component, the residual field potential, has been shown to influence V 1/2 in various channels: for instance, electroneutral mutations at the interior of the Shaker Kv channel (not expected to affect j out ) have considerable effects on V 1/2 (49)(50)(51)(52). Because the extracellular linkers L3/4, L5/P, and LP/6 were sufficient to transfer the alteration in j out we analyzed the contribution of the different components in more detail, assuming that the unchanged parts would remain relatively constant (Fig.…”
Section: Strontium Effects On Seven Wild-type Kv Channelsmentioning
confidence: 99%